The Influence of Transfer Pricing, Leverage, Profitability, and Earnings Management on Tax Avoidance Moderated by Institutional Ownership (An Empirical Study of Manufacturing Companies) - Nugroho, Danang Widhi; Sunarsih, Uun; Zulfiati, Lies (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This research delves into the multifaceted relationships between Transfer Pricing, Leverage, Profitability, Profit Management, and Tax Avoidance, with the moderating influence of Institutional Ownership in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The study employs a descriptive research design with a quantitative approach, utilizing a multiple linear regression-based method through EViews. The research population comprises manufacturing companies listed on the Indonesia Stock Exchange (BEI) between 2020 and 2021. The purposive sampling method was employed, resulting in a sample of 81 manufacturing companies, totaling 162 observations. Secondary data were collected from the official IDX website www.idx.co.id and www.yahoofinance.com. The findings indicate that Transfer Pricing and Leverage exhibit a significant positive influence on Tax Avoidance in manufacturing companies, while Profitability demonstrates a significant negative effect on Tax Avoidance. Conversely, Profit Management does not exhibit a significant impact on Tax Avoidance. Moreover, Institutional Ownership is identified as a moderator, strengthening the influence of Transfer Pricing and Leverage on Tax Avoidance. However, Institutional Ownership does not reinforce the influence of Profitability and Profit Management on Tax Avoidance. This research contributes valuable insights for policymakers, tax authorities, and corporate practitioners, highlighting the nuanced dynamics of Transfer Pricing, Leverage, Profitability, and Profit Management in shaping tax avoidance strategies, particularly in the context of manufacturing companies in Indonesia.